LNAPL saturation derived from laser induced fluorescence method - Teramoto, Elias Hideo [UNESP] (2019)
Light non-aqueous-phase liquid (LNAPL) spills are a widespread source of contamination in shallow aquifers. Owing to their human health risks, remediation actions should be undertaken to recover the contaminants from the subsurface. However, traditional investigation techniques do not assess the actual volume of residual hydrocarbon in the pore space, hindering the effectiveness of remediation predictions. The emergence of the high-resolution laser-induced fluorescence (LIF) technique has allowed the extent of NAPL migration and distribution to be determined in the field. Despite the good potential of LIF, this technique has not yet been used to quantify the volume or saturation of NAPL in porous media. By conducting medium-scale spill experiments, efforts have been undertaken to identify the empirical fluorescence signal relationship between LIF and LNAPL saturation. The comparison of both parameters indicates that LIF can predict the LNAPL saturation following an exponential function. However, owing to the high variability of the composition of LNAPL and the weathering stage, empirical coefficients to predict the saturation of LNAPL by fluorescence intensity are site-dependent. The measurement of saturation by LIF opens the possibility of more precise LNAPL volume estimation, including complex NAPL distribution scenarios.